Comparative effects of sulphonylureas, dipeptidyl peptidase‐4 inhibitors and sodium‐glucose co‐transporter‐2 inhibitors added to metformin monotherapy: a propensity‐score matched cohort study in UK primary care. Issue 5 (13th February 2020) - Wilkinson, Samantha; Williamson, Elizabeth; Pokrajac, Ana; Fogarty, Damian; Stirnadel‐Farrant, Heide; Smeeth, Liam; Douglas, Ian J.; Tomlinson, Laurie A.
Abstract: Aim: To assess the comparative effects of sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors, sulphonylureas (SUs) and dipeptidyl peptidase‐4 (DPP‐4) inhibitors on cardiometabolic risk factors in routine care. Materials and methods: Using primary care data on 10 631 new users of SUs, SGLT2 inhibitors or DPP‐4 inhibitors added to metformin, obtained from the UK Clinical Practice Research Datalink, we created propensity‐score matched cohorts and used linear mixed models to describe changes in glycated haemoglobin (HbA1c), estimated glomerular filtration rate (eGFR), systolic blood pressure (BP) and body mass index (BMI) over 96 weeks. Results: HbA1c levels fell substantially after treatment intensification for all drugs: mean change at week 12: SGLT2 inhibitors: −15.2 mmol/mol (95% confidence interval [CI] –16.9, −13.5); SUs: −14.3 mmol/mol (95% CI –15.5, −13.2); and DPP‐4 inhibitors: −11.9 mmol/mol (95% CI –13.1, −10.6). Systolic BP fell for SGLT2 inhibitor users throughout follow‐up, but not for DPP‐4 inhibitor or SU users: mean change at week 12: SGLT2 inhibitors: −2.3 mmHg (95% CI –3.8, −0.8); SUs: −0.8 mmHg (95% CI –1.9, +0.4); and DPP‐4 inhibitors: −0.9 mmHg (95% CI –2.1, +0.2). BMI decreased for SGLT2 inhibitor and DPP‐4 inhibitor users, but not SU users: mean change at week 12: SGLT2 inhibitors: −0.7 kg/m 2 (95% CI –0.9, −0.5); SUs: 0.0 kg/m 2 (95% CI –0.3, +0.2); and DPP‐4 inhibitors: −0.3 kg/m 2 (95% CI –0.5, −0.1). eGFR fell at 12 weeks for SGLT2 inhibitor and DPP‐4 inhibitor users. At 60 weeks, the fall in eGFR from baseline was similar for each drug class. Conclusions: In routine care, SGLT2 inhibitors had greater effects on cardiometabolic risk factors than SUs. Routine care data closely replicated the effects of diabetes drugs on physiological variables measured in clinical trials.